2006
DOI: 10.1111/j.1440-169x.2006.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Postembryonic epigenesis of Vasa‐positive germ cells from aggregated hemoblasts in the colonial ascidian, Botryllus primigenus

Abstract: We investigated whether Vasa was a germline-specific marker in the colonial ascidian Botryllus primigenus, and whether it was inducible epigenetically in the adult life span. We cloned a Botryllus Vasa homologue (BpVas). The deduced open reading frame encoded 687 amino acid residues. It was expressed specifically by germline cells such as the loose cell mass, oogonia and juvenile oocytes in the ovary, and the primordial testis (compact cell mass), spermatogonia and juvenile spermatocytes in the testis. The loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(115 citation statements)
references
References 59 publications
(105 reference statements)
3
109
0
Order By: Relevance
“…It is referred to as a hemoblast and is characterized by the presence of a large nucleus with a prominent nucleolus and narrow cytoplasm filled with polysomes (Wright, 1981). A variety of tissues and organs such as the gonad (Mukai and Watanabe, 1976;Sunanaga et al, 2006Sunanaga et al, , 2007, the pericardium (Nunzi et al, 1979), the pyloric gland (Kawamura and Nakauchi, 1986), and bud vesicle (Oka and Watanabe, 1957;Freeman, 1964;Sabbadin et al, 1975) differentiate from undifferentiated coelomic cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is referred to as a hemoblast and is characterized by the presence of a large nucleus with a prominent nucleolus and narrow cytoplasm filled with polysomes (Wright, 1981). A variety of tissues and organs such as the gonad (Mukai and Watanabe, 1976;Sunanaga et al, 2006Sunanaga et al, , 2007, the pericardium (Nunzi et al, 1979), the pyloric gland (Kawamura and Nakauchi, 1986), and bud vesicle (Oka and Watanabe, 1957;Freeman, 1964;Sabbadin et al, 1975) differentiate from undifferentiated coelomic cells.…”
Section: Introductionmentioning
confidence: 99%
“…During asexual reproduction, coelomic undifferentiated cells, the hemoblasts, differentiate into various tissues such as muscle cells, pyloric gland, germ cells, and multipotent epithelium (Mukai and Watanabe, 1976;Nunzi et al, 1979;Kawamura and Nakauchi, 1986a;Sunanaga et al, 2006Sunanaga et al, , 2007Sugino et al, 2007). In Symplegma reptans, hemoblasts cluster around the siphon anlagen of de- Outer and inner pharyngeal epithelia and inner longitudinal vessels were stained.…”
Section: Proliferation Dynamics Of Coelomic Cellsmentioning
confidence: 99%
“…A strong signal was also observable in loose and compact cell masses in the gonads. Both the bud primordium and germline progenitor cells are known to have an undifferentiated configuration (Manni et al, 1994;Sunanaga et al, 2006). It is, therefore, an interesting question as to whether BpMyc is related to cell proliferation or to the undifferentiated state of cells.…”
Section: Molecular Features Of Proliferating Cells In Botryllusmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators have observed that they derive from the germinal epithelium in Styela plicata (Tucker, 1942), Styela clava (Ermak, 1976), Ciona savignyi (Sugino et al, 1987(Sugino et al, , 1990, and C. intestinalis (Okada and Yamamoto, 1993). Other investigators have suggested that the primary follicle cells come from free hemoblasts of the hemocoel (Peres, 1954;De Vincentiis, 1962;Mancuso, 1965;Newberry, 1968;Mukai and Watanabe, 1976;Manni et al, 1993Manni et al, , 1995Sunanaga et al, 2006). In B. primigenus, the primary follicle cells appear to have the same origin as the PGCs, because they express a PGC-specific molecular marker at the earliest stage of differentiation (Sunanaga et al, 2006).…”
Section: B Accessory Cellsmentioning
confidence: 99%